TRANSLATION OF PHRASEOLOGICAL UNITS - M.D.Sulaymonova; U.S.Abdug’aniyeva; Bozorova Vasila Ikromovna (TADQIQOTLAR.UZ, 2025)
Annotation. Identifying and explaining the difficulties of translating phraseological units, methods to translate and examples to uzbek language.